Metabolic syndrome in Overt and Subclinical Hypothyroidism Syrian Patients - Madeline Albishara; Lama Hadid; Shaden Haddad (Acta Medica Iranica, 2022)
Thyroid hormones play an important role in several metabolic pathways including glucose and lipid metabolism and may cause metabolic syndrome. Both hypothyroidism and metabolic syndrome are common in Syrian population. This study was done to evaluate the metabolic syndrome in two types of hypothyroidism and the effect of TSH levels on its occurrence. A retrospective cross-sectional study was performed of 91 patients with overt hypothyroidism, 31 patients with subclinical hypothyroidism without clinical symptoms and 53 controls without thyroid disorders. Metabolic syndrome was defined as per International Diabetes Federation(IDF) criteria which are defined as central obesity based on race- and gender-specific WC cutoffs (Waist circumference (WC) ≥ 94cm for male , WC ≥ 80cm for female) plus